Strategi Efektif dalam Pengambilan Keputusan Manajemen Pendidikan - Herman, Annisa Robia; Annisa Nursalamah Simanjuntak; Aliyah, Rusi Rusmiati (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze in depth various effective strategies in the educational management decision-making process, especially in the context of elementary schools. The research method used is a literature review by examining various sources such as Google Scholar, Publish or Perish, and other relevant academic documents, then analyzed using content analysis by examining in depth the written information, grouping the main themes, and drawing conclusions based on the results of the analysis. This literature review found ten main managerial strategies that can be applied, ranging from data-based (Data-Based Decision Making), participatory (Participatory Approach and Participatory Decision Making), to those focused on improving internal quality (SWOT Analysis, Transformational Leadership, School Management Information Systems, Managerial Ethics, Adaptive, Contextual, and Innovative/Problem-Based Decision Making). The implementation of these strategies is crucial to creating the best learning environment, improving student learning outcomes, and preparing them to face future challenges.